Motivating Foodservice Employees to Follow Safe Food Handling Practices: Perspectives From a Multigenerational Workforce - Arendta, Susan W.; Roberts, Kevin R.; Strohbehn, Catherine; Arroyo, Paola Paez; Ellis, Jason D.; Meyer, Janell (My University, 2014)
Hospitality managers deal with a very diverse workforce, employing workers from up to four different generations, which poses a challenge for managers as they attempt to train and motivate employees. Food safety is of particular concern in foodservice organizations. This study assessed the generational differences related to foodservice employees’ perceptions of their supervisors’ roles in food safety and how supervisors could improve their effectiveness. A mixed methods approach (survey and focus groups) was used. Qualitative data analysis revealed four themes: consistency, training, managers’ behaviors, and employees’ behaviors. Based on these, best practices are suggested for motivating a multigenerational workforce.
Keywords: Foodservice supervisors; Management; Food safety; Multigenerational workforce